Label-Free, Electrical Detection of the SARS Virus N-Protein with Nanowire Biosensors Utilizing Antibody Mimics as Capture Probes - Ishikawa, Fumiaki N; Chang, Hsiao-Kang; Curreli, Marco; Liao, Hsiang-I; Olson, C. Anders; Chen, Po-Chiang; Zhang, Rui; Roberts, Richard W; Sun, Ren; Cote, Richard J; Thompson, Mark E; Zhou, Chongwu (ACS nano, 2009)
Antibody mimic proteins (AMPs) are polypeptides that bind to their target analytes with high affinity and specificity, just like conventional antibodies, but are much smaller in size (2−5 nm, less than 10 kDa). In this report, we describe the first application of AMP in the field of nanobiosensors. In2O3 nanowire based biosensors have been configured with an AMP (Fibronectin, Fn) to detect nucleocapsid (N) protein, a biomarker for severe acute respiratory syndrome (SARS). Using these devices, N protein was detected at subnanomolar concentration in the presence of 44 μM bovine serum albumin as a background. Furthermore, the binding constant of the AMP to Fn was determined from the concentration dependence of the response of our biosensors.